2016
DOI: 10.1093/jnci/djw199
|View full text |Cite
|
Sign up to set email alerts
|

Activation of STING-Dependent Innate Immune Signaling By S-Phase-Specific DNA Damage in Breast Cancer

Abstract: Background: Previously we identified a DNA damage response–deficient (DDRD) molecular subtype within breast cancer. A 44-gene assay identifying this subtype was validated as predicting benefit from DNA-damaging chemotherapy. This subtype was defined by interferon signaling. In this study, we address the mechanism of this immune response and its possible clinical significance. Methods: We used immunohistochemistry (IHC) to characterize immune infiltration in 184 breast cancer samples, of which 65 were within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
337
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 383 publications
(360 citation statements)
references
References 28 publications
18
337
1
4
Order By: Relevance
“…DDRD tumors were defined by a 44-gene expression signature associated with loss of the S-phase-specific DNA damage response and improved response to DNA-damaging chemotherapy. [102] In the study, DDRD tumors had increased IFN-related gene expression compared to non-DDRD tumors as well as increased levels of CD4 + and CD8 + T cells in the tumor and stroma[103]. Subsequent cell-based assays demonstrated that expression of the chemokines CXCL10 and CCL5, which play a key role in CD4 + and CD8 + T cell chemotaxis, increased following siRNA-mediated depletion of individual DNA repair genes (such as BRCA1 , BRCA2 , and FANCD2 ).…”
Section: Dna Repair Factors Beyond Mutational Load Can Also Impact Anmentioning
confidence: 99%
See 1 more Smart Citation
“…DDRD tumors were defined by a 44-gene expression signature associated with loss of the S-phase-specific DNA damage response and improved response to DNA-damaging chemotherapy. [102] In the study, DDRD tumors had increased IFN-related gene expression compared to non-DDRD tumors as well as increased levels of CD4 + and CD8 + T cells in the tumor and stroma[103]. Subsequent cell-based assays demonstrated that expression of the chemokines CXCL10 and CCL5, which play a key role in CD4 + and CD8 + T cell chemotaxis, increased following siRNA-mediated depletion of individual DNA repair genes (such as BRCA1 , BRCA2 , and FANCD2 ).…”
Section: Dna Repair Factors Beyond Mutational Load Can Also Impact Anmentioning
confidence: 99%
“…[103, 104] DNA-damaging agents such as cisplatin and etoposide can also increase cytosolic DNA levels in the absence of known DNA repair defects. [108] However, the mechanism by which this free DNA arises is currently not understood.…”
Section: Dna Repair Factors Beyond Mutational Load Can Also Impact Anmentioning
confidence: 99%
“…Firstly, tumours with a BRCA1/2 mutation or an HRR defect have a higher mutational burden and therefore an elevated neo‐antigen load, which is thought to elicit an increased anti‐tumour immune response . Secondly, PARP inhibitor treatment up regulates PD‐L1 expression in vivo and in vitro , and in the absence of a functional BRCA pathway there is activation of the innate immune response via the STING/TKB1/IRF3 response, which might influence the antitumor effect of a PARP inhibitor immunotherapy combination. Several different combinations of immunotherapy and PARP inhibitors are currently under evaluation in both the first‐line and relapsed settings in a variety of gynaecological cancers.…”
Section: Combination Targeted Therapymentioning
confidence: 99%
“…Enhanced expression of PD ‐L1 was also observed upon cisplatin and hydroxyurea treatments and such expression is dependent of STING activation. This observation suggests that when T‐cell infiltration and activation is therapeutically enhanced, the ensuing adaptive resistance can be overcome by a combination with PD ‐L1/ PD ‐1 blockade . (e) The anticancer efficacy of anti‐ CD 47 antibodies relies on the STING ‐dependent activation of adaptive immune responses: Chemotherapy treatment with cyclophosphamide or paclitaxel given before anti‐ CD 47 has synergistic anticancer effects, possibly due to increased DNA release from tumor cells…”
Section: A Renewed Interest In the Role Of Nucleic Acids As Danger Simentioning
confidence: 99%
“…Genomically unstable breast cancers such as BRCA1‐mutant are characterized by interferon signaling and lymphocytic infiltration . Accordingly, Parkes et al . showed that in DDRD cancer cells, the presence of cytosolic DNA activates the STING/TBK1/IRF3 pathway.…”
Section: A Renewed Interest In the Role Of Nucleic Acids As Danger Simentioning
confidence: 99%